The Impact of Rice Sharing Service on Traditional Taxy Market: Meta-analysis - Dewi, Kemala; Aris Krisdiyanto; Dewanto; Sidrotun Na'im (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
This study aims to analyze the impact of rice sharing services on the traditional taxi market through a meta-analysis. Rice-sharing services have grown rapidly in recent years, offering cheaper and more convenient transportation alternatives for consumers. The study pooled and analyzed the results of 10 studies examining the impact of rice-sharing services on the traditional taxi market. The results of the meta-analysis showed that rice sharing services had a significant negative impact on the income and number of traditional taxi passengers with an effect size value of 0.712. This effect is stronger in developing countries and in large cities. Subgroup analysis showed that the impact of rice-sharing services was greater on economy-class taxis and taxis operating on popular routes. Nan Berbagi Rice has disrupted the traditional taxi market and led to a decline in revenue and the number of traditional taxi riders. The findings have important implications for the taxi industry and policymakers looking to formulate regulations for rice-sharing services.